Copper-Induced Membrane Depolarizations Involve the Induction of Mosaic TRP Channels, Which Activate VDCC Leading to Calcium Increases in Ulva compressa - Gómez, Melissa; González, Alberto; Sáez, Claudio A.; Moenne, Alejandra (Frontiers in Plant Science, 2016)
The marine macroalga U. compressa (Chlorophyceae) is a cosmopolitan species, tolerant to heavy metals, in particular to copper. U. compressa was cultivated with 10 µM copper for 12 h and membrane depolarization events were detected. Firstly, seven depolarization events occurred at 4, 8, 12-13, 80 and 86 min, and at 5 and 9 h of copper exposure. Secondly, bathocuproine sulphonate, a specific copper-chelating compound, was added before incorporating copper to the culture medium. Copper-induced depolarizations were inhibited by bathocuproine at 4, 8, 12-13, 80 and 86 min, but not at 5 and 9 h, indicating that these events are due to copper ions entry. Thirdly, specific inhibitors of human TRPA1, C4, C5, M8 and V1corresponding to HC030031, ML204, SKF96363, M8B and capzasepin, respectively, were used to investigate whether copper-induced depolarizations were due to activation of TRPs. Inhibitor effects indicate that the seven depolarizations involved the activation of functional mosaic TRPs that displayed properties similar to human TRPA, C, M and/or V. Finally, inhibition of copper-induced depolarizations using specific human TRP inhibitors suppressed calcium increases at 2, 3 and 12 h due to activation of Voltage-Dependent Calcium Channels (VDCC). Thus, copper induces seven depolarization events that involve induction of mosaic TRPs which, in turn, activates VDCC leading to calcium increases at 2, 3 and 12 h in U. compressa.